Disappearance of Cosmology in Modern Civilization, and its Effects on Religious Life - Umair Ali; Mian Faisal Mahmood (Journal of Religion and Society, 2025)
This article examines the profound effects of secularization on modern civilization, particularly focusing on the disappearance of sacred cosmology from the Western worldview. As secularization has advanced, traditional cosmological frameworks which once provided a holistic understanding of the interconnectedness of the microcosm (human life) and macrocosm (the universe) have been replaced by a mechanistic and materialistic perspective. This shift has not only altered humanity’s relationship with nature but has also led to a spiritual and existential disenchantment. The study conducts a comparative analysis between the modern Western worldview, which prioritizes empirical and reductionist approaches, and traditional cosmological systems, which emphasize sacred symbolism, divine order, and the unity of all existence. Furthermore, the article explores the consequences of this cosmological loss on religious life, arguing that the absence of a sacred framework has contributed to the decline of spiritual meaning, ritual significance, and moral coherence in contemporary society. Additionally, the erosion of sacred cosmology has impacted various forms of knowledge, including philosophy, science, and art, leading to a fragmented understanding of reality. By analyzing these transformations, the article highlights the need for reintegrating cosmological consciousness to address the existential and ecological crises of modernity. Ultimately, this research calls for a re-examination of traditional wisdom to restore a more harmonious and meaningful engagement with the cosmos. Keywords: Secularization, Sacred Cosmology, Modern Worldview, Traditional Cosmology, Disenchantment, Religious Life, Knowledge Systems